2015
DOI: 10.4103/2347-5625.152404
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity, opinions, experiences and knowledge about scalp cooling: a Dutch survey among breast cancer patients and oncological professionals

Abstract: Objective:Scalp cooling (SC) is applied to reduce chemotherapy-induced alopecia (CIA). The aim of this study was to investigate patients’ familiarity and opinions and oncological professionals’ attitude and knowledge about SC in the Netherlands.Methods:Ex breast cancer patients, nurses and medical oncologists (MDs) from SC and non-SC hospitals filled out questionnaires.Results:The majority of MDs and nurses were satisfied with the results of SC, as were SC patients. Over 33% of MDs and nurses perceived their k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 28 publications
2
35
1
Order By: Relevance
“…The website that originated from this project supports cancer patients in preparing for CIA and enhancing expectations of its impact on daily life and provides insight into the advantages and disadvantages of scalp cooling. As scalp cooling is not always actively offered to all eligible patients,[17262728] the website might also be beneficial for patients who are searching for additional information before starting chemotherapy. The web-based tool also offers patients support in decision-making by allowing them to reflect and consider their values and opinions with regard to scalp cooling.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The website that originated from this project supports cancer patients in preparing for CIA and enhancing expectations of its impact on daily life and provides insight into the advantages and disadvantages of scalp cooling. As scalp cooling is not always actively offered to all eligible patients,[17262728] the website might also be beneficial for patients who are searching for additional information before starting chemotherapy. The web-based tool also offers patients support in decision-making by allowing them to reflect and consider their values and opinions with regard to scalp cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Those expectations are most often based on counseling by the medical doctor or oncology nurse before chemotherapy. [17] In a recent Australian study, patients recalled from the conversation with their medical doctor about the decision for scalp cooling, that they received information about efficacy, the fact that they might experience some additional hair loss despite scalp cooling, and the possibility of faster regrowth of hair. [27] Patients indicated that they would have preferred more information about the process of scalp cooling, tolerability issues and hair care, and also information to give to their hairdresser.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations